2015
DOI: 10.1186/s12984-015-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral amputee recovery strategies following trips to their sound and prosthesis sides throughout swing phase

Abstract: BackgroundRecovering from trips is challenging for transfemoral amputees, and attempts often result in falls. Better understanding of the effects of the sensory-motor deficits brought by amputation and the functional limitations of prosthetic devices could help guide therapy and fall prevention mechanisms in prostheses. However, how transfemoral amputees attempt to recover from trips on the sound and prosthesis sides throughout swing phase is poorly understood.MethodsWe tripped eight able-bodied subjects and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
4
33
1
Order By: Relevance
“…Shirota et al 164 perturbed the swing phase of both individuals with a transfemoral amputation or knee disarticulation and without an amputation. They found that both groups use similar strategies although specific strategies are used more often in one group when compared to the other.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Shirota et al 164 perturbed the swing phase of both individuals with a transfemoral amputation or knee disarticulation and without an amputation. They found that both groups use similar strategies although specific strategies are used more often in one group when compared to the other.…”
Section: Discussionmentioning
confidence: 99%
“…They found that both groups use similar strategies although specific strategies are used more often in one group when compared to the other. 164 This study was confounded by a number of factors. First of all we had a limited sample size, which affected the statistical power of the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations